2007
DOI: 10.1016/j.jcrs.2007.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted corneal welding in cataract surgery: Retrospective study

Abstract: Astigmatism was slightly affected by the use of laser welding for corneal wound closure after phacoemulsification and ECCE. The laser-assisted corneal sealing procedure was rapid and safe and could serve as an alternative to corneal suturing, with significant potential applications for the closure of longer incisions, such as those used in penetrating keratoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…In short, we found that optimized laser welding of a corneal wound could be achieved at quite low laser power densities (12-16 W/cm 2 ) and that the repair process of laser-welded corneal wounds started earlier than that of traditionally sutured wounds: objective and histological observations at two weeks after surgery showed a good morphology of laser-treated corneas, with almost restored cuts, generally characterized by lesser edematous appearance as compared to the sutured ones. The ICG solution was completely reabsorbed after three to seven postoperative days [4,5]. After 3 months the restored wound area appeared to have regained the transparency and the shape of the healthy cornea; at the microscopic level, the laser welded stroma collagen fibrils have a very linear shape and are organized in layers of regular thickness and orientation.…”
Section: Preclinical Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…In short, we found that optimized laser welding of a corneal wound could be achieved at quite low laser power densities (12-16 W/cm 2 ) and that the repair process of laser-welded corneal wounds started earlier than that of traditionally sutured wounds: objective and histological observations at two weeks after surgery showed a good morphology of laser-treated corneas, with almost restored cuts, generally characterized by lesser edematous appearance as compared to the sutured ones. The ICG solution was completely reabsorbed after three to seven postoperative days [4,5]. After 3 months the restored wound area appeared to have regained the transparency and the shape of the healthy cornea; at the microscopic level, the laser welded stroma collagen fibrils have a very linear shape and are organized in layers of regular thickness and orientation.…”
Section: Preclinical Studiesmentioning
confidence: 98%
“…The main clinical applications of CWLW are in cataract surgery [5] and in penetrating keratoplasty (i.e. full thickness transplant of the cornea).…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cataract surgery was performed on 20 patients with a preoperative visual acuity worse than 20 out of 200 [188]. Ten patients had phacoemulsification surgery and ten had extracapsular cataract extraction (ECCE).…”
Section: Laser Welding and Soldering Laser Weldingmentioning
confidence: 99%
“…The temperature enhancement induces reversible thermal denaturation in the stromal collagen, with an immediate closuring of the wound walls upon cooling. This laser welding effect was firstly demonstrated in cataract surgery 7,8 and penetrating keratoplasty 9,10 . An optimized approach that we are presenting in this paper has been studied for application in endothelial keratoplasty.…”
Section: Introductionmentioning
confidence: 94%